Onotan Syarawandan (The Message of Banda Ely's Ancestors in Community Areas Archipelago Islam) - Usman Nomay; Jamin Warwefubun (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine the meanings of onatan and the typology of syarawandan on the Banda Ely prang in the area of the Islamic Archipelago Community in Southeast Maluku Regency, Maluku Province. The research method used is the historical research method. In essence, historical research methods are carried out through four stages, namely: heuristics, source criticism, interpretation, and historiography. The results of the study show that Onotan in terms of terms are the songs of past ancestors related to religious issues, and also related to physical and so on. Onatan is also concerned with the origins of power in the village of Banda Ely.Syarahwandan means singing or telling stories about the people of Banda Ely during certain activities, such as circumcision, the implementation of the pilgrimage, state parties. This is not done at any time but only on certain religious holidays. Onatan Syarawandan typology consists of three namely; (a) The value of Aqidah in Syarawandan Lyrics, (b) Syari'ah values in Onatan Syarawandan, and (c) Moral values in Onatan Syarawandan.